Sports Competition Among the Jewish Population in Łódź in the Years 1945-1949 - Julian Jaroszewski (Jan Długosz University in Częstochowa, 2024)
The liberation of Łódź from German occupation enabled a revival of the Jewish culture, including physical culture. In the years between 1945 and 1949, Jewish people living in the city of Łódź reactivated their sporting movement. Jewish sport in Łódź did not achieve the pre-war level. The main reason was migration and a smaller Jewish population. The development of Jewish sport was adversely affected by lack of sports facilities and equipment and costly renovations of club rooms and sports fields. This resulted in the periodic suspension of sports training. The clubs that were formed: The Jewish Sports Club, Jewish Sports Club "Makabi", Jewish Chess Club, Jewish Sports Club "Jedność" ("Unity"), Jewish Workers Sports Club "Gwiazda" ("Star") competed as part of sports associations. The players of the Jewish Chess Club of Łódź were a match for the best in the country and the region. They won the Polish team championship twice (1946, 1947) and the City of Łódź championship (1947). Individually, the most successful player was Isaac Grynfeld, who won the 3rd place in the Polish championship (1946) and was 2-time Polish team champion. Among women, the Polish championship in 1949 was won by Róża Herman, PhD. The changes in Polish sport and the loss of cultural autonomy for Jews led to the dissolution of Jewish sports clubs in 1949. They were incorporated in Union Sports Club "Spójnia Solidarność" in Łódź and blended into the sporting movement created by the communist authorities.